Stephen Larigaudelle Dubuisson, S.J. (1786 - 1864) and the reform of the American Jesuits - Buckley, Cornelius M. (Univ. Press of America, 2013)
Cornelius Michael Buckley, S.J. delves into Stephen Larigaudelle Dubuisson's life, using him as the point of departure to describe the tensions among Jesuits in Maryland after the restoration of the order in 1814. A refugee of the violent slave rebellions in Haiti, where he was born, and the Terror in France, Dubuisson became a clerk in Napoleon's personal treasury and a resident in the Tuileries. He was a member of Marie Louise's flight in 1814 and later differed with Napoleon's account of the fate of the lost treasury during this momentous event. The following year, giving up a promising career in the Restoration government, he entered the slave-owning Jesuits in Maryland. Ten years later, he was the priest involved in the Mattingly Miracle. After a brief tenure as Georgetown's fourteenth president, Dubuisson spent three years in Europe advising the Jesuit general how to keep his American troops in step along the Ignatian "long black line." During this time, he began his career as a fundraiser and propagandist for the American Church and as an unofficial, and sometimes vexing, diplomat of the general in the courts of Europe. After his return, Dubuisson served as a parish priest in Virginia, Maryland, and Pennsylvania. Elected a second time to represent the Maryland Jesuits at a meeting in Rome, he never returned to the United States and eventually became chaplain to the dashing Duke and Duchess de Montmorency Laval. Recognized as "the chief pillar of the Jesuit mission in the United States," he died in Pau, France, during the height of the American Civil War.--Publisher